Indications for Surgical Therapy in Chronic Pancreatitis Operationsindikationen bei der chronischen Pankreatitis - Müller-Debus, Charlotte Friederieke; Wellner, Ulrich Friedrich; Bösch, Florian; Belyaev, Orlin; Brunner, Maximilian; Radulova-Mauersberger, Olga; Grützmann, Robert; Uhl, Waldemar; Witzigmann, Helmut; Werner, Jens; Keck, Tobias (Zentralblatt für Chirurgie, 2020)
Chronic pancreatitis is a recurrent disease with repeating exacerbations of inflammation of the pancreatic gland - associated with belt-like back pain. Without treatment, recurrent chronic pancreatitis leads to development of opioid-dependent pain. The chronic pancreatitis leads to recurrent hospital stays for the affected patient and socioeconomic challenges. In progress it can lead to local complications of chronic pancreatitis, such as formation of pseudocysts, biliary duct obstruction, duodenal obstruction or portal hypertension. The aim of this article is a detailed description of the indication for surgical therapy in chronic pancreatitis. The underlying analysis was a systematic literature research and evaluation, the formulation of key questions according to the PICO system and the evaluation of indications and key statements and questions, as implemented in a three level Delphi process among the members of the pancreas research group and the indications for the surgery group of the German Society of General and Visceral Surgery (DGAV). Surgical resection of the inflammatory pancreatic head pseudotumour, after initial conservative therapy, is a highly efficient therapy for the control of pain and the avoidance of complications in chronic pancreatitis. For this purpose, well evaluated surgical strategies are available. Delay in surgical therapy can lead to chronic pain, kachexia and malnutrition and increase complications of surgical therapy.
CRIS-Team Scopus Importer:2020-08-14
Keywords: chronic pancreatitis; indication; pancreas; PICO; surgery